Study on the influence of surfactant medium on the key functional group of methane adsorption in medium rank coal - Jinlu WANG; Feng CAI (Meikuang Anquan)
In order to study the effect of surfactants on the key functional groups on the surface of medium rank coal, 12 kinds of surfactants were selected to treat the raw coal, and the microchemical structure of the surface of the coal samples was determined by infrared spectroscopy. Using infrared semi-quantitative parameterization, four structural parameters, namely maturity, fatty chain length, aromaticity and condensation, were calculated; the effects of surfactants on the methane adsorption capacity of coal were investigated according to the changes of the chemical structural parameters of the coal samples. The results showed that the surfactant did not change the structure of the coal, but affected the intensity of the absorption peaks and the ratio of functional groups in the coal. After treatment with surfactants, the maturity of coal samples decreased, the fatty chain became shorter, the aromaticity increased, and the condensation was enhanced; in particular, the maturity parameter of the coal sample treated with 1% APG0814 solution increased by 0.31, the fatty chain length parameter decreased by 0.25, the aromaticity parameter increased by 0.18, and the aryl cyclic condensation parameter increased by 0.37, and the consideration of the structural parameter and the methane adsorption ability linkage, it was concluded that the concentration of 1% APG0814 solution had the greatest effect on the adsorption capacity of coal and promoted the desorption of methane from coal.